2010
DOI: 10.1103/physrevb.81.014514
|View full text |Cite
|
Sign up to set email alerts
|

Boson-fermion duality and metastability in cuprate superconductors

Abstract: The intrinsic structural metastability in cuprate high-T c materials, evidenced in a checkerboard domain structure of the CuO 2 planes, locally breaks translational and rotational symmetry. Dynamical chargedeformation fluctuations of such nanosize unidirectional domains, involving Cu-O-Cu molecular bonds, result in resonantly fluctuating diamagnetic pairs embedded in a correlated Fermi liquid. As a consequence, the single-particle spectral properties acquire simultaneously ͑i͒ fermionic low-energy Bogoliubov b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…They are mutually coupled through the charge exchange (Andreev-type) scattering. Such scenario (31) has been considered by various authors in the context of high T c superconductivity [14][15][16][17][18][19][20][21] and for description of the resonant Feshbach interaction in the ultracold fermion atom gasses [36][37][38].…”
Section: Superconducting Fluctuationsmentioning
confidence: 99%
See 4 more Smart Citations
“…They are mutually coupled through the charge exchange (Andreev-type) scattering. Such scenario (31) has been considered by various authors in the context of high T c superconductivity [14][15][16][17][18][19][20][21] and for description of the resonant Feshbach interaction in the ultracold fermion atom gasses [36][37][38].…”
Section: Superconducting Fluctuationsmentioning
confidence: 99%
“…More recently [19] we have also investigated evolution of the k-resolved pseudogap considering two-dimensional lattice dispersion with the nearest and next-nearest neighbor hopping integrals realistic for the cuprate superconductors. For temperatures slightly above T c we have found that the pseudogap starts to close around the nodal points restoring the Fermi arcs, whereas in the antinodal areas the pseudogap practically does not change.…”
Section: A Outline Of the Continuous Diagonalizationmentioning
confidence: 99%
See 3 more Smart Citations